Making and Testing Sample Control on Determination of Nitrite Content in Water and Wastewater by Using UV-Visible Spectrophotometer - Erna Styani; Endang Sri Lestari; Ika Widiana; Muhammad Ramadhan (Journal of Environmental Engineering and Waste Management, 2019)
This study focused on Making and Testing sample  control as reference material on determination of nitrite content in water and waste water by using UV-Visible Spectrophotometer. Sample control has been made to replaced Certified Reference Materials (CRM) for  determination of Nitrite content in water and waste water by using UV -Visible  Spectrophotometer. Substitute materials for CRM should be homogeneous and stable, so the homogenity and stability control sample that has been made in this study  is tested by using standard referring to ISO Guide 35 , 2006. The result of   this experiments shows that    the values of Fstat and Ftable  on homogenity test are  0.796 and 3.179 (Fstat <  Ftable); while the values of  tstat and table  on the stability test are 0.431 and 2.101 (tstat <  table),  the mean of control sample concentration is 0,0435 mg / L. All test parameters have been qualified in accordance with ISO Guide 35 , 2006. The result of this  research shows  that the control of samples on the determination of Nitrite in water and waste water by using UV-Visible Spectrophotometer can be used as  substitute for CRM and reference material.